2000
DOI: 10.1159/000022136
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Concentrations in Relation to Sick Euthyroid Syndrome in Elderly Patients with Nonthyroidal Illnesses

Abstract: Background: Leptin, the ob gene product, seems to be involved in regulating energy expenditure in humans, but its role in the pathophysiology of the energy imbalance in chronically ill patients is largely unknown. Objective: To evaluate plasma leptin concentrations and thyroid function in elderly patients with nonthyroidal illnesses (NTI). Methods: Sixty-four NTI elderly patients (75.0 ± 6.3 years, 27 males and 37 females) and 21 age- and sex-matched healthy controls (73.0 ± 5.5 years, 9 males and 12 females) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The average concentrations in older subjects with normal weight are similar to those observed in other studies for controls Ͼ60 years of age (10,52,53). The mean numbers coincide with investigations that show that the older subjects present higher serum leptin levels than young adults (20,31,50,52).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The average concentrations in older subjects with normal weight are similar to those observed in other studies for controls Ͼ60 years of age (10,52,53). The mean numbers coincide with investigations that show that the older subjects present higher serum leptin levels than young adults (20,31,50,52).…”
Section: Discussionsupporting
confidence: 88%
“…There is scientific evidence showing that leptin is involved in the initiation of puberty, pregnancy, breast‐feeding, immune system regulation, inflammatory processes, respiratory function, sex hormones, growth hormone, and thyroid hormones, in addition to bone tissue metabolism, septic processes, hematopoiesis, cachexia, and others (6, 7, 8, 9, 10, 11, 12, 13, 14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…Serum leptin levels decrease during fasting as well as in elderly patients with the euthyroid sick syndrome, leading to subsequent decrease in TSH levels (27). These changes likely serve as an adaptive mechanism to reduce catabolic process and energy expenditure in the setting of acute illness (9,27,106). Increased hypothalamic D2 activity as well as increased Triac production also have been reported to directly decrease TSH production, similar to what has been observed in the pituitary (14).…”
Section: Alterations In Thyroid-stimulating Hormone Secretionmentioning
confidence: 67%
“…Leptin has been reported to directly regulate TRH production, and leptin and TSH levels are directly related to each other (15,54,75). Serum leptin levels decrease during fasting as well as in elderly patients with the euthyroid sick syndrome, leading to subsequent decrease in TSH levels (27). These changes likely serve as an adaptive mechanism to reduce catabolic process and energy expenditure in the setting of acute illness (9,27,106).…”
Section: Alterations In Thyroid-stimulating Hormone Secretionmentioning
confidence: 99%
“…The same may be occurring in some cases of euthyroid sick syndrome. It has been reported that among elderly patients with chronic non-thyroidal illnesses, those who presented low serum free thyroxine (T4) and free T3 -as well as high reverse T3 -also had low concentrations of serum leptin (Corsonello et al 2000). In addition, hypothyroid patients may show decreased serum leptin (Valcavi et al 1996), although there is some disagreement in published reports (Zimmermann-Belsing et al 2003) and so far a consistent relationship between serum concentrations of leptin and thyroid hormone has not been established.…”
Section: Introductionmentioning
confidence: 99%